Analysis of The Balanced Scorecard Implementation at Divisional Level in PT KPC to Rebuild Contextual Map for MOD Performance Management System - Meiliza, .; Wibisono, Dermawan (The Indonesian Journal of Business Administration, 2015)
Abstract – The Balanced Scorecard is one of Performance Management System invented by Kaplan and Norton that is widely used in many companies in the world. KPC (PT. Kaltim Prima Coal) started the Balanced Scorecard implementation at the end of year 2013 in three divisions; one of them was Mining Operation Division (MOD). But, according to observation during one year of implementation at the end of year 2014, it seemed that MOD management never used the Balanced Scorecard for performance review. Thus, a study was conducted to seek and analyze the root causes of the problem. In this study, researcher used purposive sampling because those being interviewed were chosen based on their position in the company. Primary data was gathered by doing interviews and discussion. Meanwhile, the sources of secondary data were company’s historical documents regarding Balanced Scorecard implementation in KPC.During interviews and discussions, it was concluded that there were three main aspects which caused the balanced Scorecard implementation failure. Current Balanced Scorecard strategy map, software used for scorecard automation, and implementation process itself were three main aspects that were being analyzed. The analyses results showed that there were three root causes of the problem; those were incomplete strategy map structure, limited software capability, and premature implementation. To solve the problem researcher suggests MOD to rebuild its current MOD Balanced Scorecard strategy map and modify software setting to solve limited software capability. The researcher also suggests MOD to involve personnel from other divisions which activities are related to MOD activities.